2016
DOI: 10.1161/strokeaha.115.011979
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cost-Effectiveness of Ambulatory Cardiac Rhythm Monitoring After Cryptogenic Stroke

Abstract: Background and Purpose-Prolonged ambulatory ECG monitoring after cryptogenic stroke improves detection of covert atrial fibrillation, but its long-term cost-effectiveness is uncertain. Methods-We estimated the cost-effectiveness of noninvasive ECG monitoring in patients aged ≥55 years after a recent cryptogenic stroke and negative 24-hour ECG. A Markov model used observed rates of atrial fibrillation detection and anticoagulation from a randomized controlled trial (EMBRACE) and the published literature to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 40 publications
3
21
0
1
Order By: Relevance
“…Post-stroke ECG monitoring is likely costeffective. 74,79 However, RCTs have not been powered to assess the effect of prolonged ECG monitoring on stroke or mortality.…”
Section: Special Cases: a Ischemic Stroke And Embolic Stroke Of Undementioning
confidence: 99%
“…Post-stroke ECG monitoring is likely costeffective. 74,79 However, RCTs have not been powered to assess the effect of prolonged ECG monitoring on stroke or mortality.…”
Section: Special Cases: a Ischemic Stroke And Embolic Stroke Of Undementioning
confidence: 99%
“…Eight articles were excluded mainly, but not exclusively, because they did not report on health economic outcome parameters [12, 13, 14, 15, 16, 17, 18, 19]. Three articles were excluded because the intervention was not a DHI aimed at secondary stroke prevention [20, 21, 22], 7 articles were excluded because they were reviews after thorough screening of the reference list [15, 23, 24, 25, 26, 27, 28], 1 article because it was a study protocol [29], and another article because the stroke patients were not the target population [30]. Zero papers were withheld for inclusion in this review.…”
Section: Resultsmentioning
confidence: 99%
“…This issue was addressed in several papers in the literature. Yong et al [253] suggested prolonged ECG monitoring for secondary stroke prevention, which eventually eliminates the cost of stroke treatment consequences. Additionally, prolonged and active monitoring significantly improved the diagnosis of AF and was associated with significantly lower emergency department visits and hospitalization requirements [254].…”
Section: Performance-based Monitoring Systemsmentioning
confidence: 99%